Human Factors and Reliability Engineering for Safety and Security in Critical Infrastructures Decision Making, Theory, and Practice - De Felice, Fabio; Petrillo, Antonella; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book collects a high-quality selection of contemporary research and case studies on the complexity resulting from human/reliability management in industrial plants and critical infrastructures. It includes: Human-error management issues-considering how to reduce human errors as much as possible. Reliability management issues-considering the ability of a system or component to function under certain conditions for a specified period of time. Thus, the book analyses globally the problem regarding the human and reliability management to reduce human errors as much as possible and to ensure safety and security in critical infrastructures. Accidents continue to be the major concern in "critical infrastructures", and human factors have been proved to be the prime causes to accidents. Clearly, human dynamics are a challenging management function to guarantee reliability, safety and costs reduction in critical infrastructures. The book is enriched by figures, examples and extensive case studies and is a valuable reference resource for those with involved in disaster and emergency planning as well as researchers interested both in theoretical and practical aspects.
The Importance of Human Error and Reliability Management in Critical Conditions and Infrastructures -- An Overview on Human Error Analysis and Reliability Assessment -- Mathematical Models for Reliability Allocation and Optimization for Complex Systems -- Integrated Engineering Approach to Safety, Reliability, Risk Management and Human Factors -- A Fuzzy Modeling Application for Human Reliability Analysis in the Process Industry.
Keywords: Security systems; Mechanical engineering; Operations research; Security Science and Technology; Mechanical Engineering; Operations Research and Decision Theory